The Reasoned Action Approach to Growth Intention to Increase Small And Medium Enterprises: A Conceptual Framework - Annuridya Rosyidta Pratiwi Octasylva; Yuliati Lilik Noor; Hartoyo; Agus W Soehadi (School of Business, IPB University (SB-IPB), 2021)
Entrepreneurship plays an important role in the economy, among others, in reducing the unemployment rate and improving the economy of a country. However, this was not accompanied by the interest of entrepreneurs in increasing their business. Even though interest is the main predictor in shaping the behaviour and performance of a business. This article aimed to provide literature on what factors can shape an entrepreneur's interest in developing his business. In answering the objectives of this study, a literature study was carried out on the articles about interest in developing a business published in the 2010-2021 period and contained in a bibliographic database. Based on the results of the study, four factors could strengthen the interest in entrepreneurs developing their business, namely: attitude, descriptive norms, injunctive norms and perceived behavioural control with the theoretical approach of reasoned action approach, which are known to be better at predicting behavioural interest because the variables used are more detailed. This research is not only useful for entrepreneurs to increase their demand to develop their business but also useful for related stakeholders to support the increase in-class promotion of MSME actors. Keywords: attitude, descriptive norm, MSME, injunctive norm, perceived behavioural control